Location Estimation Utilising WiMAX Preamble Detection Under ITU-R Channel Models - Awang Md Isa, Azmi; Johal, Muhammad Syahrir; Mohd Zin, Mohd Shahril Izuan; Mohamad Isa, Mohd Sa'ari (2013)
In this paper, a novel mobile WiMAX location and positioning scheme utilizing WiMAX preamble has been proposed. The purpose of the scheme is to enhance the accuracy of location estimation in WiMAX services. Preamble detection for 10MHz and 20MHz FFT bandwidth under ITU-R channel models (Vehicular (A) and Pedestrian (B)) has been evaluated and analysed. Simulation results show that the 20MHz FFT outperformed the 10MHz bandwidth under various channel models. Best result for preamble detection in mobile WiMAX is best achieved when the mobile station is in low velocity with higher FFT bandwidth.